EXPLORING THE EFFECTS OF PATERNAL OBESITY AND TAURINE INTERVENTION ON SEMINAL VESICLE FLUID COMPOSITION AND PLACENTAL DEVELOPMENT - Jazwiec, Patrycja (My University, 2025)
Paternal obesity increases the risk of pregnancy complications and predisposes children to metabolic disease in adulthood. These outcomes are underpinned by placental dysfunction. While it is well established that paternal obesity alters the sperm epigenome, impacts on the seminal vesicle fluid composition and downstream effects on placental development are not fully understood. We hypothesized that paternal obesity-associated metabolic compromise induces a pro-inflammatory shift in seminal vesicle fluid, impairing maternal decidual spiral artery transformation, and precedes insufficient placental perfusion and hypoxia at mid-gestation and late gestation. We also hypothesized that taurine intervention rescues obesity-associated metabolic compromise and seminal vesicle fluid composition, mitigating placental vascular changes. We tested this hypothesis using a mouse model of paternal high fat diet-induced obesity with metabolic compromise. In Chapter 2, we showed that placentas sired by obese males were hypoxic at mid-gestation and late gestation, with a compensatory angiogenic response but impaired blood vessel integrity. In Chapter 3, we demonstrated that obesity resulted in profound changes in seminal vesicle fluid cytokine and chemokine composition largely driven by adiposity in the father, and was associated with modest placental hypoxia manifesting earlier in gestation. However, placental hypoxia induced by paternal obesity was not accompanied by alterations in peripheral maternal immune cell composition or marked impairments in arterial transformation. In Chapter 4, we demonstrated that a 10-week taurine intervention did not fully rescue obesity-associated reproductive or metabolic compromise in obese males. Furthermore, in the control context, taurine negatively impacted placental vascular structures, suggesting that it was ineffective as an intervention for obesity in the father and detrimental in the absence of obesity. Overall, our findings indicate that paternal obesity-induced placental dysfunction characterized by reduced placental oxygenation was not preceded by maternal peripheral immune changes or impaired spiral artery transformation. However, obesity induced profound changes in seminal vesicle fluid cytokine and chemokine composition in a manner that influenced pregnancy success. We also showed that taurine intervention did not rescue metabolic compromise in the father and was not associated with improved placental outcomes. These new data provide insight into the mechanisms underpinning suboptimal placental function in pregnancies generated by obese fathers and clarifies the effectiveness of taurine intervention in the father in mitigating these effects.
IMPACTS OF PATERNAL OBESITY AND TAURINE INTERVENTION ON THE PLACENTA